Assessment of technical efficiency of Business Administration Courses in Brazil - Soliman, Marlon; Siluk, Julio Cezar Mairesse; Neuenfeldt Júnior, Alvaro Luiz; Casado, Frank Leonardo (Revista de Administração da UFSM, 2017)
This study aimed to conduct an assessment of the technical efficiency of Business Administration courses in Brazil, by means of Data Envelopment Analysis (DEA), a nonparametric technique introduced by Charnes, Cooper and Rhodes (1978). Were used as variables in the model the eight component indicators of the Preliminary Concept of Course (CPC) to evaluate 1229 courses of Business Administration based on the results of the National Examination of Performance Evaluation of Students (ENADE) of 2009, obtaining as result that only 1.2% of these can be considered efficient. After this measurement, a step of recommendations was made to propose goals for the inefficient courses, thus bringing to light that better results can achieved given the inputs already available for Business Administration courses.